Letter (copy) : Spanish workers' children and Christmas - Tewson, Vincent
032-0182-001 International. HVT/WJB/AT/286 6th December, 1938. Mr. W. Schevenels, International Federation of Trade Unions, 9 Avenue D'Orsay, Paris, VIIe. Dear Comrade Schevenels, SPANISH WORKERS' CHILDREN CHRISTMAS We duly received your letter of the 5th instant and are glad to know that you are getting into touch with Comrade Santiago concerning the idea that was suggested of brightening Christmas time for the children of the Spanish workers. We quite agree with you that while it is most desirable that something on these lines should be done, and indeed, for all the children in territory under the Spanish Republican Government, it is going to be extraordinarily difficult. We have concentrated on getting as much foodstuff as possible to send to Spain, as we understood the need was so urgent, and so far as that branch of our work is concerned we are pleased to say that we are making arrangements to send the largest consignment hitherto shipped, so that distribution can take place about Christmas time. Yours faithfully, Assistant Secretary. 292/946/32/182